Legitimacy of The CJEU In the Settlement of Trade Mark Disputes of Non-European Union Foreign Companies: A Case Study - Annas Rasid Musthafa; Satriya Aldi Putrazta; A’an Efendi (Lampung Journal of International Law, 2023)
Protection of Intellectual Property Rights(IPR) in the industrial world is an urgency for companies to maintain popularity in the general public, Especially on the use of trademarks that greatly affect consumer perceptions. One of the problems in trademark protection is the existence of dispute resolution through court under a supranational organization, namely The Court of Justice of The EU(CJEU), which adjudicates foreign companies originating from non-EU countries. The case is a trademark dispute between China Construction Bank Corp from China and Groupement des cartes bancaires from France.The purpose of this study is to determine the authority and legitimacy as well as the application of justice through The CJEU in resolving disputes of foreign companies. This research was a normative legal research method, which applied to statue approach, case study research, and library research. Based on the results of the research, the authority and legitimacy of The CJEU in resolving disputes with foreign companies has been regulated in the Maastricht treaty and the submission of foreign companies is also related to the opposing party which is a company flagged by a member state of the EU. The use of the CJEU in resolving disputes requires parties to maximize all judicial remedies available at the national level first before proceeding to the international level.